2019
DOI: 10.1007/s00421-019-04226-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of New Zealand blackcurrant extract on sport climbing performance

Abstract: Purpose Blood flow to skeletal muscles and removal of metabolic by-products during a sport climb are essential to optimise performance and recovery. New Zealand blackcurrant 2 (NZBC) extract enhanced blood flow and performance in other exercise modalities. We examined the effect of NZBC extract on sport climbing performance and recovery. Methods The study employed a double-blind, randomized, cross-over design. Male sport climbers (n=18, age 24±6 yrs, height 179±6 cm, mass 71.4±7.8 kg, French grade 6a-8b) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
0
28
0
3
Order By: Relevance
“…However, because the group observations indicate an effect of NZBC extract on iMVC forces but not twitch forces, it is possible that voluntary performance may be enhanced via a central mechanism. Many studies have reported performance-enhancing effects by intake of New Zealand blackcurrant extract [ 4 , 5 , 6 , 7 , 8 , 9 ]. It is possible that the variation in individual responses to New Zealand blackcurrant extract in previous studies may be partly due to fiber-type specific effects during exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the group observations indicate an effect of NZBC extract on iMVC forces but not twitch forces, it is possible that voluntary performance may be enhanced via a central mechanism. Many studies have reported performance-enhancing effects by intake of New Zealand blackcurrant extract [ 4 , 5 , 6 , 7 , 8 , 9 ]. It is possible that the variation in individual responses to New Zealand blackcurrant extract in previous studies may be partly due to fiber-type specific effects during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In general, an anthocyanin is a flavonoid with potential anti-oxidant and anti-inflammatory properties providing health benefits [ 3 ]. Studies with anthocyanin-rich New Zealand blackcurrant extract have provided observations on the performance-enhancing effects for a 16.1 km cycling time trial [ 4 ], repeated high-intensity treadmill running [ 5 ], two 4 km cycling time trials [ 6 ], repeated sprints in the running-based anaerobic sprint test [ 7 ], maximal sprints in the Loughborough Intermittent Shuttle Test [ 8 ], and sport climbing [ 9 ]. The mechanisms for the performance-enhancing effects of New Zealand blackcurrant extract are unknown, but may be due to enhanced blood flow [ 10 ] and muscle oxygenation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Cook et al (16), New Zealand blackcurrant supplementation for seven days modulated blood flow at rest and during a single sustained submaximal isometric contraction, but did not affect muscular performance. In comparison, blackcurrant supplementation for the same duration was found to improve cycling trial time (17), running time to exhaustion (15), and sport climbing performance (18) in trained volunteers. Although hemodynamics were not measured in these latter studies, these findings highlight that increases in exercise performance gained from blackcurrant intake may be dependent on the mode of exercise.…”
Section: Introductionmentioning
confidence: 92%
“…Intensity as low as 10 % of maximum voluntary isometric contraction (iMVC) force partially occludes forearm blood flow and can negatively impact muscle performance (21), while full occlusion occurs with intensities of 50-60% iMVC (24,25); such forces are likely to occur during sports where the athlete grasps an opponent or supports their body weight during climbing, for example. The potential for handgrip performance to be improved by blackcurrant supplementation was shown by Potter et al (18) who demonstrated an improvement in sport rock climbing performance after 7 days of supplementation, however it is unclear if any benefit is achieved with a single dose of blackcurrant extract and whether such improvement is related to changes in hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Blackcurrant concentrate also improved forearm blood flow in machine typists (Matsumoto et al, 2005). Only one study examined effects of NZBC extract in rock climbers (Potter et al, 2019). Potter et al (2019) observed that 7-days loading of NZBC extract enhanced exhaustive treadwall climbing distance by 15%.…”
Section: Introductionmentioning
confidence: 99%